Improving physical and mental health in women with breast cancer undergoing anthracycline-based chemotherapy through wearable device-based aerobic exercise: a randomized controlled trial - Li, Hongmei; Sang, Die; Gong, Lijing; Wang, Boliang; Wang, Yong; Jia, Xiao; Yu, Jingjing; Kong, Zhenxing; Liu, Haiyun; Zhang, Yimin (Frontiers in Public Health, 2024)
Purpose: Aimed to assess the impact of wearable device-based aerobic exercise on the physical and mental well-being of women with breast cancer (BC) undergoing chemotherapy.Methods: Forty adult women with BC who underwent anthracycline-based chemotherapy were randomly allocated to the exercise group (n=21) or the control group (n=19). Both groups received standard health education and oncology care. In addition, the exercise group wore wearable devices to engage in moderate to highintensity (50%-90% HRmax) aerobic exercise during chemotherapy, while the control group did not carry out exercise intervention. Health-related physical fitness level, physical activity energy expenditure (PAEE), anxiety and depression scores, sleep quality, cancer-related fatigue, and overall quality of life (QoL), were assessed both before (prior to the first chemotherapy session) and after (prior to the fifth chemotherapy session) the exercise intervention. Exercise-related adverse events, exercise compliance, number and severity of gastrointestinal reactions and myelosuppression occurred were recorded during the exercise intervention.Results: After the intervention, compared to the control group, the exercise group (1) had significantly higher relative VO2peak (P=0.003) and handgrip strength (P<0.001);(2) had significantly higher PAEE (P<0.001); (3) had a significantly lower scores in anxiety (P=0.007), depression (P=0.028), sleep quality in domains of subjective sleep quality (P=0.010), sleep disturbances (P=0.004), daytime dysfunction (P=0.007), cancer-related fatigue in domains of physical (P<0.001) and affective (P<0.001); and(4) had a significantly lower scores in QoL in domains of physical well-being (P<0.001) and emotional well-being (P=0.019), while a significantly higher scores in functional well-being (P<0.001). Patients in the exercise group experienced less severe gastrointestinal reactions (P=0.028) and myelosuppressive symptoms (P<0.001) than that in the control group. Patients in the exercise group had no serious exercise-related adverse events, with a mean exercise adherence of 81.8%.Wearable device-based aerobic exercise during chemotherapy can be an effective adjunctive therapy to improve physical and mental health in BC patients.Trial registration: This trial was registered on Chinese Clinical Trial Registry (ChiCTR2300073667).